2018
DOI: 10.1371/journal.pone.0197699
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and central adiposity: A Brazilian study with a representative sample of the public health system users

Abstract: ObjectiveTo assess the association between indicators of psychosocial stress and central adiposity in adult users of the Unified Health System (SUS) from Southeast of Brazil.MethodsThis cross-sectional study was conducted with 384 adults (20 to 59 years old) from the city of Alegre, Southeastern Brazil. The simple random sample represented the population using the public health system of the municipality. The prevalence of obesity was based on the Body Mass Index, and central adiposity (dependent variable) was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…Sleep tends to be interrupted in menopause due to hormone fluctuations and declines [48]. Studies have also found that a lack of sleep stress level [17][18][19][20]48], and a high level of stress is associated with increased risk for obesity [49]. Interventions that target sleep hygiene and stress management are critical to reducing obesity risk among postmenopausal women in China.…”
Section: Plos Onementioning
confidence: 99%
“…Sleep tends to be interrupted in menopause due to hormone fluctuations and declines [48]. Studies have also found that a lack of sleep stress level [17][18][19][20]48], and a high level of stress is associated with increased risk for obesity [49]. Interventions that target sleep hygiene and stress management are critical to reducing obesity risk among postmenopausal women in China.…”
Section: Plos Onementioning
confidence: 99%
“…Nutritional or developmental stages may explain the relationship between body size and GCR expression. Food insecurity and malnutrition has been found to stimulate stress and increase cortisol levels in humans (Sawaya 2006; Freitas et al 2018), which in turn could influence stress hormone receptor expression (Cottrell & Seckl 2009). Alternatively, it may be that stress responsiveness, as altered GC-receptor expression, may influence energy resources allocated between stress and growth, seen as varying growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…Excess weight is also related to chronic inflammation through NFκB pathways; however, no association between overweight and methylation status has been previously reported for the NR3C1 gene 62 . It is possible that hypomethylation of this region may be related to low-grade inflammation, a feature of the overweight state 63 .…”
Section: Discussionmentioning
confidence: 99%